Smoking and its relation to the histological type, survival, and prognosis among patients with primary lung cancer - Xavier, Flávio; Henn, Lucélia de Azevedo; Marja, Oliveira; Orlandine, Luciane (São Paulo Medical Journal, 1996)
The frequency of smoking among patients with primary lung cancer diagnoses admitted to the Hospital de Clinicas de Porto Alegre (HCPA) during the 1980's was investigated. The objective of this study was to analyze cigarette consumption patterns through the number of cigarettes smoked per day and the age at which smoking began, correlating this data to the overall survival rate and histological type of the lung cancer. Methods: This retrospective study analyzed patients with primary lung cancer diagnosed at the HCPA between January 1980 and December 1989. All patients considered underwent follow-up for at least three years. Patient information was obtained either from the hospital's records or by contacting patients via letter or phone. Results: More than 90 percent of the patients were smokers or had smoked previously; most had started smoking before the age of 20.The overall 24-month survival rate after diagnosis varied depending on whether the patient had smoked less than 40 cigarettes per day or not. The percentage of smokers and non-smokers was established for each histological type, with the bronchoalveolar adenocarcinoma type showing the highest percentage of non-smokers (40 percent). Conclusion:The overall survival rates of patients with lung cancer was related to the number of cigarettes smoked, and not to the fact of the patient having smoked or not.The number of smokers among patients with lung cancer was not so high only for the bronchoalveolar adenocarcinoma histological type.